Macromolecular composition and anaerobic degradation of the sludge produced in a sequencing batch reactor - Chelme, Susana; Fonseca, Pamela; Mercado, Rodrigo; Alarcón-Pulido, Nelson A.; Sánchez, Omar (Electronic Journal of Biotechnology, 2008)
The effect of sequencing batch reactor (SBR) operating conditions on sludge macromolecular composition and the effect of sludge macromolecular composition on the anaerobic degradation of the sludge produced in SBR was investigated in this work. A SBR, fed with synthetic wastewater, was operated at different air flow rates. The resulting sludge was analyzed in terms of protein, carbohydrate, phospholipid and polyhydroxybutyrate concentrations. Methane production during anaerobic digestion of the sludge was also measured. Ammonium, nitrite, nitrate, dissolved oxygen and chemical oxygen demand (COD) track studies in the SBR were carried out in order to relate SBR performance and sludge macromolecular composition. The lowest air flow rate at which the SBR was operated was 2 l min-1, in which case the dissolved oxygen concentration was lower than 0.5 mg l-1 in the SBR and partial denitrification occurred during the feeding phase. An increased air flow rate caused a decrease in protein concentration, as well as an increase in carbohydrate concentration. Polyhydroxybutyrate (PHB) concentration in the sludge was independent of air flow rate. At different air flows, the methane production rates were similar, but the total volume of methane was greater during anaerobic digestion of the sludge produced at low air flow rates. These results indicate a strategy by which changes in sludge composition can optimize the operation of anaerobic sludge digesters.